Reclaiming and Reimagining Macro Social Work Education: A Collective Biography. (2nd April 2016) - Netting, F. Ellen; O'Connor, Mary Katherine; Cole, Portia L.; Hopkins, Karen; Jones, Jenny L.; Kim, Youngmi; Leisey, Monica; Mulroy, Elizabeth A.; Rotabi, Karen Smith; Thomas, M. Lori; Weil, Marie O.; Wike, Traci L.
ABSTRACT: The authors focus on a collective biography of 12 women social work educators, all either tenured or in tenure lines, from five different universities at the time of the study. The participants represent several aspects of macro practice including administration, planning, community practice, and policy. Beginning with reflections about coming into macro practice, we highlight memories about first teaching experiences and examine cultural shifts discovered in our academic journeys. We feature students who inspired us and perceptions of challenges in curricular development affecting the preparation of students. This article includes comments that emphasize the themes and focus of our collective reflections. Finally, we place what we learned in the context of a report from the Association for Community Organization and Social Administration calling for the visibility of and advocacy for macro social work education.